2021
DOI: 10.21303/2504-5679.2021.001622
|View full text |Cite
|
Sign up to set email alerts
|

Central Hemodynamics and Oxygen Transport in Patients With Acute Respiratory Distress Syndrome Caused by Covid-19 and Their Impact on the Course and Outcomes of the Disease

Abstract: The aim. Determine hemodynamic status and its impact on oxygen transport, frequency of adverse events and outcomes in patients with severe SARS-CoV-2 associated with acute respiratory distress syndrome (ARDS). Materials and methods. A single-center prospective comparative study was conducted with 29 patients enrolled over the period of July—October 2020 who suffered a severe course of coronavirus disease and bilateral pneumonia associated with ARDS. Based on the estimated cardiac index (CI), patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 21 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Biomarkers of mitochondrial dysfunction reported in the included studies were: mitochondrial DNA (mtDNA) (eight studies) ( 6 , 10 16 ) glutathione coupled mediators [(referenced retrospectively, glutathione, glutanation, glutathione S -transferase (GST), L-gluatamate and glutathione perosidase)] (five studies) ( 17 21 ), lactate (three studies) ( 20 , 22 , 23 ), malondialdehyde (MDA) (three studies) ( 17 , 24 , 25 ), metabolic signaling pathways and mediators [(referenced retrospectively: Nicotinamide adenine dinucleotide (NADH), N-terminal peptide FMNPLAQ - also known as NADH2, glyceraldehyde-3-phosphate dehydrogenase-like 6 (GAPDHL6), sirtuin enrichment, xanthine and hypoxanthine)] (four studies) ( 26 29 ), oxidative stress associated markers [(hydrogen peroxide (H 2 O 2 ), super oxidase dismutase (SOD), ascorbate, alpha tocopherol, beta-carotene and retinol] (three studies) ( 24 , 30 , 31 ) ( Table 3 ). Notably, multiple studies reported more than one biomarker, as recorded in Tables 2 – 5 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Biomarkers of mitochondrial dysfunction reported in the included studies were: mitochondrial DNA (mtDNA) (eight studies) ( 6 , 10 16 ) glutathione coupled mediators [(referenced retrospectively, glutathione, glutanation, glutathione S -transferase (GST), L-gluatamate and glutathione perosidase)] (five studies) ( 17 21 ), lactate (three studies) ( 20 , 22 , 23 ), malondialdehyde (MDA) (three studies) ( 17 , 24 , 25 ), metabolic signaling pathways and mediators [(referenced retrospectively: Nicotinamide adenine dinucleotide (NADH), N-terminal peptide FMNPLAQ - also known as NADH2, glyceraldehyde-3-phosphate dehydrogenase-like 6 (GAPDHL6), sirtuin enrichment, xanthine and hypoxanthine)] (four studies) ( 26 29 ), oxidative stress associated markers [(hydrogen peroxide (H 2 O 2 ), super oxidase dismutase (SOD), ascorbate, alpha tocopherol, beta-carotene and retinol] (three studies) ( 24 , 30 , 31 ) ( Table 3 ). Notably, multiple studies reported more than one biomarker, as recorded in Tables 2 – 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies (41%) reported numerical trends toward association of higher levels of mitochondrial biomarkers with higher mortality, however the association did not reach statistical significance, or insufficient numerical information was provided ( 17 , 23 , 27 , 29 32 ). Positively but non-significantly associated with mortality biomarkers consisted of: xanthine ( 30 ), glutathione, MDA ( 17 ), ascorbate, alpha-tocopherol ( 31 ), GAPDHL6 ( 27 ), glutathione peroxidase (selenium) ( 21 ), mediators of sirtuin signaling pathway, mediators of oxidative phosphorylation ( 29 ) and lactate ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations